(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2022)
Technological evolution and the appearance of digital environments have ended up affecting the fundamental rights of people and it has been foressen that new rights or new existing rights are protected with powers. Orgaanic Law 3/2018, of December 5, about Protection of Personal data and guarantee of digital rights has regulated, for the first time in our legal system, as such a category specifies, the so called digital rights. A significant advance in a path in wich much remains to be resolved. On june 14, 2021, the Government addopted the Digital Rights Charter, a constant document of regulatory effectiveness that represents another step in the process and a highly qualified starting point of subsequent regulations in the matter.